Full mtDNA genome sequencing of Brazilian admixed populations: A forensic-focused evaluation of a MPS application as an alternative to Sanger sequencing methods. (September 2019) - Avila, E.; Graebin, P.; Chemale, G.; Freitas, J.; Kahmann, A.; Alho, C.S.
Highlights: Full mitochondrial genome sequences were generated for 96 Brazilian samples by MPS. Sequencing performance evaluation and haplotype classification is presented. Comparative analysis was performed for control region Sanger-generated sequences. Interpopulation comparison of Brazilian and 26 worldwide populations was executed. Technique adequacy for Brazilian forensic laboratories casework reality is discussed. Abstract: The use of Massive Parallel Sequencing (MPS) techniques have been proposed by the forensic community as an alternative to Sanger sequencing methods in routine forensic casework analysis regarding mitochondrial DNA (mtDNA). Interesting features of MPS include high throughput, ability to simultaneously genotype a significant number of samples by barcoding techniques, processing automation, reduced time and costs, among others. Advantages include the capability of generating full mtDNA genome sequences versus usual techniques, usually limited to hypervariable or control regions exclusively. In this work, 96 reference single-source samples from three different Brazilian cities were subjected to full mtDNA genome sequencing by MPS techniques using an early-access version of Precision ID mtDNA Whole Genome Panel on an Ion Torrent PGM platform (Thermo Fisher Scientific, Waltham, MA, USA). Complete, high-quality sequences were obtained and sequencing performance was evaluated via four different metrics. As a subset of evaluated samples have been previously submitted for Sanger sequencing of the control region, a comparative analysis of both methods' results was conducted in order to compare technique adequacy within a forensic context. Even though this study is one of the first to report full mtDNA genome sequences for Brazilian admixed populations, the observed haplotypes exhibit a predominance of Native American and African maternal lineages in the studied sample set, reproducing results described in the literature for control regions only. Interpopulation analysis among Brazilian and 26 worldwide populations was also carried out. The results indicate that MPS-generated full mtDNA genome sequences may have great utility in forensic real casework applications, with a pronounced gain of genetic information and discrimination power provided by coding region evaluation and the enhanced capacity of heteroplasmies determination. Database construction and other relevant factors concerning implementation of such techniques in Brazilian forensic laboratories are also discussed.